[Agricultural Business Management students with calculator] (1967)
This photo was printed in the 1968 El Rodeo Yearbook, pg. 129. The caption says "Calculating is based on all profit after completing the Agricultural Business Management major at Cal Poly. Front to back: Jeanne Wylie, Kathy Gonzales, Don Hordness, Rich Willard, and Rex Wisnand."